Aktywność i zaangażowanie imigrantów jako wymiary partycypacji publicznej: Polskie stowarzyszenia i inicjatywy na Islandii - Małgorzata Budyta-Budzyńska (University of Warsaw, Centre of Migration Research (CMR), 2016)
– This paper describes the origins of Polish diaspora structures in Iceland. To this end, and with reference to the theory of civic participation, we point out two analytic categories: the association activity of the immigrants understood as their capacity for self-organization and creation of community events, and the engagement of the immigrants given by their participation in such events. In the second part, we describe the major Polish associations and informal initiatives, and apply to them a variant of SWOT analysis. In the final part we describe the divisions within the leadership of the Polish community in Iceland and the issues faced by Polish associations there.
Keywords: 330; Poles in Iceland; immigrant associations; divisions among Polish diaspora; problems faced by Polonia associations